Designing the user interface : strategies for effective human-computer interaction. - Shneiderman, Ben, ....-; Plaisant, Catherine, ....- (Boston : Pearson Education, 2005)
In 1996, recognizing this book, ACM's Special Interest Group on Documentation (SIGDOC) presented Ben Shneiderman with the Joseph Rigo Award. SIGDOC praised the book as one "that took the jargon and mystery out of the field of human-computer interaction" and attributed the book's success to "its readability and emphasis on practice as well as research." In revising this best-seller, Ben Shneiderman again provides a complete, current, and authoritative introduction to user-interface design. The user interface is the part of every computer system that determines how people control and operate that system. When the interface is well designed, it is comprehensible, predictable, and controllable; users feel competent, satisfied, and responsible for their actions. In this book, the author discusses the principles and practices needed to design such effective interaction. Based on 20 years experience, Shneiderman offers readers practical techniques and guidelines for interface design. As a scientist, he also takes great care to discuss underlying issues and to support conclusions with empirical results. Interface designers, software engineers, and product managers will all find here an invaluable resource for creating systems that facilitate rapid learning and performance, yield low error rates, and generate high user satisfaction. Coverage includes the human factors of interactive software (with added discussion of diverse user communities), tested methods to develop and assess interfaces, interaction styles (like direct manipulation for graphical user interfaces), and design considerations (effective messages, consistent screen design, appropriate color).
Keywords: Gebruikers-interfaces.